Pharmacist Services - Olson, Anthony (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The overall goal of this book is to give the reader a state-of-the-art synopsis of the pharmacist services domain. To accomplish this goal, the authors have addressed the social, psychosocial, political, legal, historic, clinical, and economic factors that are associated with pharmacist services. In this book, you will gain cutting-edge insights from learning about the research of experts throughout the world. The findings have relevance for enhancing pharmacist professionalism, pharmacist practice, and the progression of pharmacist services in the future.